Severe Renal Hemorrhage in a Pregnant Woman Complicated with Antiphospholipid Syndrome: A Case Report - Shohei Kawaguchi; Kouji Izumi; Takahiro Nohara; Tohru Miyagi; Hiroyuki Konaka; Atsushi Mizokami; Eitetsu Koh; Mikio Namiki (Advances in Urology)
Antiphospholipid syndrome is a systemic autoimmune disease with thrombotic tendency. Consensus guidelines for pregnancy with antiphospholipid syndrome recommend low-dose aspirin combined with unfractionated or low-molecular-weight heparin because antiphospholipid syndrome causes habitual abortion. We report a 36-year-old pregnant woman diagnosed with antiphospholipid syndrome receiving anticoagulation treatment. The patient developed left abdominal pain and gross hematuria at week 20 of pregnancy. An initial diagnosis of left ureteral calculus was made. Subsequently abdominal-pelvic computed tomography was required for diagnosis because of the appearance of severe contralateral pain. Computed tomography revealed serious renal hemorrhage, and ureteral stent placement and pain control by patient-controlled analgesia were required. After treatment, continuance of pregnancy was possible and vaginal delivery was performed safely. This is the first case report of serious renal hemorrhage in a pregnant woman with antiphospholipid syndrome receiving anticoagulation treatment and is an instructive case for urological and obstetrical practitioners.